FAKTOR-FAKTOR PENYEBAB ANAK PUTUS SEKOLAH (Studi Madrasah Ibtidayah (MI) Dan Madrasah Tsanawiyah (MTs) Nurul Wathan Pusaran 8 Kecamatan Enok Kabupaten Indragiri Hilir) - Sutiasnah, Resi Anggun; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to examine the causes of school dropouts in Madrasah Ibtidayah (MI) and Madrasah Tsanawiyah (MTs) Nurul Wathan Pusaran 8 Sub-District Enok, District of Indragiri Hilir. The method used in this research is descriptive quantitative, with a population of 37 people, because the population is not too much, then it is done by census. The collection data obtained by using the method of observation, interview and documentation. Technical analysis of the data using quantitative descriptive analysis method. Based on the results it can be concluded that there are four reasons of dropout children in Madrasah Ibtidayah (MI) and Madrasah Tsanawiyah (MTs) Nurul Wathan Pusaran 8 Sub-District Enok, District of Indragiri Hilir. The factors are: (1) Economic factor 89,19%, (2) Social environment factor 86,49%, (3) Factor of their own accord 59,46% and (4) The motivation of parents 51,35%. so, the most dominant factor that causes dropouts are economic factors.Keywords: MI and MTs dropouts, descriptive quantitative analysis.